(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article Caputo in the sense of fraction in order private derivative differential equation for mixed issue we learn This in the article right issue solve and In Caputo’s sense show that the solution of the partial differential equation of fractional order exists and is unique , and it is intended to obtain results related to the correct problem of determining the source function caught.